Processing of gammaTiAl, by ceramic crucible induction melting, and pouring in ceramic shells - Barbosa, J. (2003)
The production of high quality titanium and titanium alloys castings is a difficult and expensive task. The main reasons for that are: the high melting point; the extremely high reactivity of titanium alloys against a large amount of elements (solid, liquids and gaseous) at high temperatures, with particular emphasis to oxygen. For this reason, traditional casting techniques and materials cannot be used, both for the melting and the moulding operations, and melting and pouring have to be performed under vacuum or inert gas. However, such demands are extremely important factors to the high cost of titanium castings, and one possible way to decrease it might be the use of traditional casting techniques, with slight changes both on materials and production equipments and procedures. This paper describes the production technique of TiAl castings, using a multi-layered refractory crucible based on stabilized zirconia, and pouring in different refractory investment casting shells. Microhardness and residual elements concentration profiles, from the surface to the inside of castings, characterization of the metal-mould interface, and surface finish of samples will be presented and discussed, and results compared with the available bibliographic references, for this kind of alloy